PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN RUMAH MAKAN PONDOK PATIN H.M. YUNUS PEKANBARU - Wahyudi Al Fajar Muhammad; Zulkarnain Zulkarnain; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The rapid development of the culinary business in Indonesia has resulted in tougher competition in the culinary business. This makes culinary business people must be able to attract and retain customers by improving product quality and service quality. One of the famous and long-lasting restaurants, Pondok Patin H.M. Yunus Pekanbaru. This study aims to determine the effect of product quality and service quality on customer satisfaction and loyalty at Pondok Patin H.M. Yunus Pekanbaru. Primary data retrieval was carried out using questionnaires to 100 respondents who had been selected using the Incidental Sampling technique and then the primary data was processed using the Structural Equation Modeling analysis method with SmartPLS version 3. The results showed that: 1) Product Quality on Customer Satisfaction had positive results. positive and significant. 2). Service Quality on Customer Satisfaction has positive and significant results. 3). Product Quality on Customer Loyalty has positive and significant results. 4). Service Quality towards Customer Loyalty has positive and significant results. 5). Customer Satisfaction with Customer Loyalty has positive and significant results. 6). Customer satisfaction partially mediates between Product Quality and Customer Loyalty with positive and significant test results. 7). Customer satisfaction partially mediates between Service Quality and Customer Loyalty with positive and significant test results. Keywords: Product Quality, Service Quality, Customer Satisfaction, Customer Loyalty, Pondok Patin H.M. Restaurant Yunus.